Electropulse-induced microstructural evolution in a ferritic–pearlitic 0.14% C steel. (February 2015) - Rahnama, A.; Qin, R.S.
Abstract : The present work reports the experimental observation of electropulse-induced microstructural evolution in a ferritic–pearlitic steel at ambient temperature. Electropulsing initially causes the fragmentation of lamellar structure. Further treatment leads to the formation of new cementite plates aligned with the current direction. This is attributed to the reduction of the system free energy. The hardness of the material decreased with an increase in the number of electric current pulses. Electrical resistivity is thought to be responsible for the observed phenomenon.